Brand Personality Dimension for Islamic Educational Institution - Imron Muttaqin (Indonesian Journal of Islamic Education Studies (IJIES), 2023)
This study explored the factors influencing brand personality that can be used in Islamic education institutions. The general dimension of brand personality is first dialogued with Islamic teachings. The research used a qualitative method with a literature approach and qualitative content analysis. The primary data were journal articles from reputable publishers and libraries online; Elsevier, Springer, Emerald, SciELO, Scientific Journal Publishers Limited, and accredited national journal with second rank selected by two considerations; citations and their relevance with the study's purpose. This study revealed that Islamic education institutions could use brand personality dimensions; sincerity, responsibility, openness, competence, lively, ruggedness, and emotion. Further researchers are expected to explore brand dimensions and create indicators based on Islamic teachings.